PENGARUH KUALITAS PELAYANAN PUSKESMAS TERHADAP KEPUASAN PASIEN PENGGUNA KARTU PEMELIHARAAN KESEHATAN MASYARAKAT SURAKARTA (PKMS) DI SURAKARTA - Nunuk Herawati; Nur Qomariyah (STIE AUB Surakarta, 2015)
This study aims are to determine the effect of tangible, reliability, responsiveness, assurance and emphaty variables toward the pasients satisfaction of PKMS cards user in Surakarta. The hypothesis are that thre are significant effect of tangible, reliability, responsiveness, assurance, and emphaty toward the patients satisfaction of PKMS cards users in Surakarta. This research is a survey. Data used primary data collected through questionnaires to the patients of PKMS cards user at “Puskesmas” in Surakarta. The data tested by using validity, reliability, classical assumption test, multiple regression analysis, t test, f test and R2 test. The t test result shows that tangible, reliabilty, responsiveness, assurance have a positive and significant effect on patients of PKMS cards user in surakarta. While the empathy variable is negative effect but significant on patients.